I saw the light [videorecording (DVD)] - Abraham, Marc, 1949 May 28-; Hiddleston, Tom; Olsen, Elizabeth, 1989-; Jones, Cherry, 1956-; Whitford, Bradley; Escott, Colin (Sony Pictures Home Entertainment, 2016)
The story of the legendary country western singer Hank Williams, who in his brief life created one of the greatest bodies of work in American music. The film chronicles his meteoric rise to fame and its ultimately tragic effect on his health and personal life.